Prevention of infectious diseases in athletes - Luke, A.; d'Hemecourt, P. (Clinics in Sports Medicine, 2007)
The sports medicine physician may face challenging issues regarding infectious diseases when dealing with teams or highly competitive athletes who have difficulties taking time off to recover. One must treat the individual sick athlete and take the necessary precautions to contain the spread of communicable disease to the surrounding team, staff, relatives, and other contacts. This article reviews preventive strategies for infectious disease in athletes, including immunization recommendations and prophylaxis guidelines, improvements in personal hygiene and prevention of spread of infectious organisms by direct contact, insect-borne disease precautions, and prevention of sexually transmitted diseases. A special emphasis on immunizations focuses on pertussis, influenza, and meningococcal prophylaxis.